A dialética nas fronteiras da convivência: o movimento dos sujeitos a partir de uma escola técnica industrial em direção ao mundo do trabalho - Nascimento, Claudio Rodrigues do (2018)
This study is related to the research line 2 – Educational Practices and Public Policies, of the Graduation Program on Education, Kairós Group – Group of researches and studies about Work, Education and Public Policies, both, of Federal University of Santa Maria/Rio Grande Sul State/ Brazil. This research aimed at analysis and comprehension of the movement and the insertion of students that carried out educational technical courses, at Santa Maria's Industrial Technical School that, in majority, have entered the world of work. Recognizing the dynamics and the transition that have happened in geographical spaces and historical times of Schools and Companies, this work aimed at setting up the real needs of the subjects involved, since their internship to their experience in the market/world of work. It came from the assumption that making an educational technical course can influence decisively in the configuration of coexistence boundaries among subjects, determining their real conditions of life and the coping with market-world of work, job and employability. Understanding the boundaries of coexistence between subjects implies knowing concretely the reality, the sociocultural forms and relations to and between groups (and subjects) with which coexist and produce social existence. In this dense space are work, education, the interests of the State and of the subjects, political, social, economic impositions, philosophical and ideological positions linked in a network of presuppositions that historically surround these boundaries. All these pretensions and possibilities are immersed in a capitalist system that is on the side of the ruling class against the workers. The research was based on the dialectic analysis, understood as a critical possibility of the phenomena comprehension, based on Historical Materialism. From categories as education, work, mediation, praxis, historicity and contradiction, it was made discourse analysis of the semistructured questionnaire and of the individual interviews with sixty five subjects. It is important to point out the achievement of the interlocution group as an important space of debate and of reconstitution of blows around the boundaries of coexistence and the dynamics between the professional technical education (PTE) and the world of work. The PTE is constituted on the subjects speech as a space of production of possibilities of life, young and adults, through the movement of their lived realities and of transformation of knowledge. The subjects ratify the importance of Professional Education for their joining and permanence in the world of work. It is important that the investments in the PTE scope make possible the joining to the different knowledge fields; that the technical courses were integrated to the Brazilian high school; and that the pedagogical work produce a praxis meaning of emancipation and the transformation of society.